EFFECT OF DIFFERENT MODES OF POLLINATION ON FRUIT SET, FRUIT WEIGHT AND SEED NUMBER IN KIWIFRUIT [ FRUIT WEIGHT AND SEED NUMBER IN KIWIFRUIT [Actinidia Actinidia deliciosa deliciosa (A. Chev (A. Chev.) C. F .) C. F. LIANG AND A. R. FERGUSON] . FERGUSON] - DINESH SINGH; S. SIAG.; KUMAR,K; V. S. RANA; NIRMLA CHAUHAN (The Bioscan, 2019)
The present investigation was carried out to study the effect of different modes of pollination on fruit set; fruit weight and seed number in kiwifruit during 2015-16. Four pistillate cultivars viz. Hayward, Bruno, Monty and Allison and two staminate cultivars viz. Allison and Tomuri of kiwifruit were selected for the study. A high (95.55-100 %) percent fruit set was observed under hand pollination in comparison with (83.28-93.99 %) open pollination in the various cultivars. The fruit retention percentage under hand pollination was higher (82.45-100 %) than (77.41-90.32 %) that of open pollination across all the cultivars. Fruit size was proportionate to the number of seeds; fruits with maximum numbers of seeds were largest in size. Maximum fruit weight (98.50 %) and number of seeds (1060.33) was observed with hand pollination compared to open pollination. Under different modes of pollination hand pollination was found beneficial in improving the fruit quality of kiwifruit over open pollination. Therefore hand pollination is recommended in kiwifruit to get quality production.